A Novel Oncogenic Driver in a Lung Adenocarcinoma Patient Harboring an EGFR-KDD and Response to Afatinib - Chen, Dong; Li, Xing-liang; Wu, Biao; Zheng, Xiao-bin; Wang, Wen-xian; Chen, Hua-fei; Dong, Yi-yu; Xu, Chun-wei; Fang, Mei-yu (Frontiers in Oncology, 2020)
Introduction: Oncogenic mutations in the epidermal growth factor receptor (EGFR) occur frequently in patients with lung cancer. These mutations may serve as critical predictive biomarkers in patients with non-small cell lung cancer (NSCLC). Among them, EGFR exon 18–25 kinase domain duplication (EGFR-KDD) mutations have been identified as a novel EGFR gene subtype in NSCLC. Case Presentation: We reported a rare case of a 59-year-old male diagnosed with adenocarcinoma. A biopsy revealed an EGFR-KDD identified by the next generation sequencing (NGS). Effective treatment outcome has been observed after administration with afatinib. Conclusion: This case highlights that comprehensive NGS technique is valuable in detecting novel genetic mutations in tumors.